Mitral Valve Prolapse In Patients With Benign Joint Hypermobility Syndrome (BJHS) - Mohammed, Tariq Jassim; Mohammed, Tariq Jassim (AL-Kindy College Medical Journal, 2019)
Background: Joint hypermobility  was first mentioned by Hippocrates as an isolated feature, when he described the Celts' Incapacity to Pull a Bowstring or Throw a Dart, Due to The Slackness of Their LimbsObjective: to determine the prevalence of mitral valve prolapse(MVP)in patients with benign hypermobility syndrome (BJHS).Type of the study: Cross –sectional study.Methods: Ninety patients with BJHS were included in this study. Full cardiological assessment was done for all of them,  which  include clinical examination, electrocardiography and echocardiography. Cardiac assessment was done for another sixty age and sex matched (normal mobile) Individuals served as a control group. Statistical analysis was done by using T test or chi square as indicated.Results: Among 90 patients with BJHS, MVP was reported in 26 patients (28.9%) compared to four individuals (6.7%)of the control group on modern echocardiography studies (P=0.013).Conclusions: the prevalence of MVP was significantly higher among patients with BJHS compared to normal mobile individuals.